2004
DOI: 10.1007/s10350-004-0589-9
|View full text |Cite
|
Sign up to set email alerts
|

Sacral Neuromodulation in Patients With Fecal Incontinence: A Single-Center Study

Abstract: Sacral neuromodulation is a feasible treatment option for fecal incontinence in patients with structurally intact sphincters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
77
1
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(89 citation statements)
references
References 48 publications
10
77
1
1
Order By: Relevance
“…The median follow-up period was 29.2 months (range 6.5-60.0) and the median period between the last AR and the PNE was 3 years (range [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. All had an intact anal sphincter determined by endo-anal ultrasound.…”
Section: Group Amentioning
confidence: 99%
See 1 more Smart Citation
“…The median follow-up period was 29.2 months (range 6.5-60.0) and the median period between the last AR and the PNE was 3 years (range [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. All had an intact anal sphincter determined by endo-anal ultrasound.…”
Section: Group Amentioning
confidence: 99%
“…In 1995, Matzel et al [12] published their results of SNM applied to faecal incontinence. Since then, many studies demonstrated the efficacy of SNM for the treatment of faecal incontinence [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Sacral nerve stimulation was first used in patients with urinary bladder dysfunction [13] and later, on with a high success rate, in patients with faecal incontinence [14][15][16]. The minimally invasive two-step procedure of sacral nerve stimulation with percutaneous nerve evaluation, together with placement of the percutaneous lead, was performed at our institution without any complications.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with conventional test electrode had a median Wexner score of 13.5 (range, [8][9][10][11][12][13][14][15][16] and those with tined lead 15 (range, 6-20); p=0.553. All patients received single dose antibiotics preoperatively (1000 mg cefazolin and 500 mg metronidazole intravenously).…”
Section: Methodsmentioning
confidence: 99%
“…Most FI is caused by an interaction of various pathophysiological factors, including abnormal anorectal sensation, colorectal motility as well as anatomical changes to the pelvic floor and sphincter complex [1][2]. Nevertheless, it mainly affects females as a result of direct damage to the anal sphincter(s) or indirect damage caused by stretching of the pudendal nerve during childbirth [3]. This common problem, which persists especially in older population, leads to physical and psychological disability and social isolation.…”
Section: Introductionmentioning
confidence: 99%